2008
DOI: 10.1007/s00066-008-1946-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stereotactic radiosurgery (SRS) alone and whole brain radiotherapy (WBRT) plus a stereotactic boost (WBRT + SRS) for one to three brain metastases

Abstract: WBRT+SRS resulted in better IC and LC but not better OS than SRS alone. Because also IC and LC are important end-points, additional WBRT appears justified in patients with one to three brain metastases, in particular in RPA class I patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 24 publications
9
38
0
1
Order By: Relevance
“…Median survival 3.4 mo, 1-y survival 12%, ie, comparable results Survival of the contemporary cohort analyzed here is comparable to representative large cohorts from the current decade Knisely et al, 16 Rades et al, 17,18 Suh et al 19 These studies confirm the survival results obtained with SRS, surgery, or WBRT in the current analysis clear, statistically significant observation was the increase in female patients with brain metastases in the contemporary cohort (57% vs 30%, P < .0001), resulting primarily from an increase in the number of female patients with lung cancer (56% of the contemporary lung cancer patients were females compared with 11% in the historical cohort, P < .0001). This shift could be driven by 2 factors, one being an obvious increase in the absolute numbers of women developing lung cancer and therefore subsequent brain metastases, as has been reported in other studies, but also possibly by a worrisome preliminary observation that women with lung cancer may be more susceptible to developing brain metastases compared with men.…”
Section: Argument References Commentsupporting
confidence: 81%
“…Median survival 3.4 mo, 1-y survival 12%, ie, comparable results Survival of the contemporary cohort analyzed here is comparable to representative large cohorts from the current decade Knisely et al, 16 Rades et al, 17,18 Suh et al 19 These studies confirm the survival results obtained with SRS, surgery, or WBRT in the current analysis clear, statistically significant observation was the increase in female patients with brain metastases in the contemporary cohort (57% vs 30%, P < .0001), resulting primarily from an increase in the number of female patients with lung cancer (56% of the contemporary lung cancer patients were females compared with 11% in the historical cohort, P < .0001). This shift could be driven by 2 factors, one being an obvious increase in the absolute numbers of women developing lung cancer and therefore subsequent brain metastases, as has been reported in other studies, but also possibly by a worrisome preliminary observation that women with lung cancer may be more susceptible to developing brain metastases compared with men.…”
Section: Argument References Commentsupporting
confidence: 81%
“…Though the prognosis of brain metastases is associated with multiple factors such as age, performance status, and lack of extra cerebral metastases (Gaspar et al, 1997), the result still remains the same in the RPA class I and RPA class II group. However, Rades et al showed that the 1-year survival rate was higher in the WBRT plus SRS group than in the SRS group, which may associated with age≤61 years, RPA classⅠ, less brain metastases, longer interval from tumor diagnosis to irradiation and lack of extra cerebral metastases (Rades et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Two studies (Sneed et al, 2002;Rades et al, 2008) that contains 162 patients evaluated the 1-year survival rate of RPA class I, there is no heterogeneity between them (p=0.73, I 2 =0%), the fixed effects model was used, the result showed that there was no significant statistics difference between the two groups (OR=1.08, 95%CI: 0.56~2.07; p=0.82) (Figure 3). …”
Section: Rpa Class I: 1-year Survival Ratementioning
confidence: 99%
See 1 more Smart Citation
“…There is no difference in the clinical outcome whether radiotherapy or neurosurgery is used as an intervention. SRS is mainly advocated in situations with one to three metastases [6,27,38,41], while some studies allow up to five lesions [3,49]. Commonly, a single lesion is treated by a surgical approach.…”
Section: Metastasesmentioning
confidence: 99%